AKTIVITAS ANALGETIKA EKSTRAK N-HEKSANA, ETIL ASETAT DAN ETANOL BUAH BELIMBING WULUH (Averrhoa bilimbi L.) PADA MENCIT JANTAN GALUR SWISS WEBSTER DENGAN METODE GELIAT - Patonah Hasbalah (Universitas Bhakti Kencana, 2014)
Tests were conducted to Averrhoa bilimbi L. as analgesic activity in male Swiss Webster mice by Siegmund method. A number of 55 male mice were randomly divided into 11 groups: group 1 (received suspension drug carrier), group 2 (received aspirin dose of 65 mg / kg bw), group 3-5 (received n-hexane extracts doses of 5, 50 , 500 mg / kg bw respectively orally), group 6-8 (received ethyl acetate extracts doses of 5, 50 , 500 mg / kg bw respectively orally), and group 9-11 (received ethanol extracts doses of 5, 50 , 500 mg / kg bw respectively orally). Induction of pain using 1% acetic acid dose of 262.5 mg / kg bw intraperitoneally. Data amount of stretching for 1 hour each group were analyzed statistically. The results showed that the Averrhoa bilimbi L. extracts of n-hexane, ethyl acetate and ethanol showed analgesic activity. Ethanol extract of Averrhoa bilimbi L. dose of 500 mg / kg bw showed analgesic activity comparable to aspirin.Based on the results of this study concluded that Averrhoa bilimbi L. have analgesic activity. Averrhoa bilimbi L. extract as the best analgesic is ethanol extract dose of 500 mg / kg bw.